Detour Polynomial of Theta Graph - Abdullah, Herish O.; Omar, Zhian I.; Ali, Ahmed M. (Iraqi Journal of Science, 2023)
Let be any connected graph with vertices set and edges set . For any two distinct vertices and , the detour distance between and which is denoted by is a longest path between and in a graph . The detour polynomial of a connected graph is denoted by ; and is defined by . In this paper, the detour polynomial of the theta graph and the uniform theta graph will be computed.